Leading disadvantaged learners : from feeling a failure to achieving success - Middlewood, David; Abbott, Ian, 1955-; Pamas, Roberto (London, England : Zed Books, 2021)
"Where schools working in adverse conditions are achieving outstanding learning outcomes, what is it that these schools do to achieve these outcomes? Are there common factors here which could apply everywhere, or at least in the vast majority of circumstances? Drawing on a range of research, including interviews with children, parents, teachers and school leaders in rural and urban contexts in England, Greece, India, Malaysia, Seychelles, South Africa, Tanzania, and the USA, the authorship team explores these important questions. The excitement and enthusiasm for, and a commitment to, learning in which every single person there was involved seems to underpin the achievement. While this often sprang from the school's leaders, who set the tone and were highly visible inspirations to everyone else, leadership was found at every level of these schools with people feeling empowered to lead and manage in the way that worked for 'their' learners. The book is filled with case studies, showcasing examples of children and young people who have overcome huge disadvantages in their lives and circumstances to achieve their potential at school. These children and young people are not 'super heroes' but mostly children with normal abilities and talents who have succeeded thanks to highly effective work and strategies by leaders, teachers, and staff in their schools. Whilst some of the obstacles which prevent disadvantaged children from achieving in education can only be removed through changing features of certain education systems themselves, there are clear identifiable strategies to be used and actions that can be taken in any school to raise the achievement of those children from disadvantaged contexts. After describing and analysing the causes and consequences of various kinds of disadvantage, the book puts forward key principles and show how they underpin actions and strategies for leaders and others to apply in their schools, at whole school, classroom and individual level"--
List of Figures Preface Part I: Disadvantaged Learners: Causes and Consequences -- 1. The Context of Disadvantage and Under-Achievement in Education -- 2. Who Are The Disadvantaged Learners? -- 3. The Causes of Disadvantage and Under-Achievement -- 4. The Implications of Under-Achievement in School -- 5. The Consequences of Under-Achievement in School Part II: Addressing the Problem -- 6. The Key Principles for Action -- 7. School Leadership and Management -- 8. Collaboration -- 9. Staff Training and Development -- 10. Community Involvement -- 11. Applying the Principles: An Extended Case Study in the US, Roberto A -- . Pamas Part III: Conclusions and Proposals -- 12. Conclusions and Proposals References Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Children with social disabilities -- Education -- Cross-cultural studies; Academic achievement -- Cross-cultural studies; Management: leadership & motivation; Electronic books